2017
DOI: 10.1177/1354816617701440
|View full text |Cite
|
Sign up to set email alerts
|

Examining domestic and international visits in Australia’s Aboriginal tourism

Abstract: Using recent nationwide panel data, an analysis considering the factors that influence the choice of Aboriginal tourism was undertaken. Although international visit numbers were larger than domestic, the former and not the latter is found to be on a decline over time. Gender does not influence domestic visits but females among international visitors are more likely to participate in Aboriginal tourism. Evidence also shows that international marketing strategies aimed at first-time visitors and adult couples, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, domestic consumers dispersed outside capital cities, much more than international arrivals, visiting regional Australia for 63% of their trips. This is extremely positive for the support and economic development of smaller regional areas, among them Indigenous communities in remote areas, an integral part of Australian society (see Mahadevan, 2018;Abascal et al, 2016, and references therein for studies related to Australian indigenous tourism).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, domestic consumers dispersed outside capital cities, much more than international arrivals, visiting regional Australia for 63% of their trips. This is extremely positive for the support and economic development of smaller regional areas, among them Indigenous communities in remote areas, an integral part of Australian society (see Mahadevan, 2018;Abascal et al, 2016, and references therein for studies related to Australian indigenous tourism).…”
Section: Introductionmentioning
confidence: 99%
“…Through their own analysis, Ruhanen et al (2015) found that not only is the level of awareness of Indigenous tourism opportunities low amongst domestic and international tourists-25% and 20% respectively-but that those with a preference for engaging in Indigenous tourism experiences comprise only 12% of all tourists and those with the intention to participate sit at just 2%. Along with low tourist awareness, a general domestic tourist malaise due to 'backyard' familiarity appears to exist (Mahadevan 2017) and ambivalence that can be partially ascribed to the impact of negative media attention on remote Indigenous communities (Ruhanen et al 2015). High travel costs to remote locations and the constraints of limited vacation time may add further doubt to tourist decision making (Akbar 2016;Ruhanen et al 2015).…”
Section: Indigenous Cultural Tourism and Australia's Territory Arts Tmentioning
confidence: 99%
“…Some of the perceived barriers to the uptake of Indigenous tourism have been identified in the literature (Akbar 2016;Mahadevan 2017;Pomering and White 2011;Ruhanen et al 2015): perceptions that Indigenous tourism is 'inauthentic;' concerns regarding remote travel; perceptions that Indigenous tourism experiences are not diverse and are already familiar to domestic tourists, along with the effect of damaging racial stereotypes and negative media attention. If these barriers to tourist participation are recognised by art centres, there is potential to address them.…”
Section: Art Centre Websites Social Media and Cultural Tourismmentioning
confidence: 99%